Collecting the Holocaust: private collections of Holocaust mementos in post-1945 Central and East-Central Europe - Waligórska, Magdalena (Holocaust and genocide studies, 2025)
Private collections featuring Holocaust-related objects, either in the form of daily objects of Jewish life or representations thereof, are an under researched source of knowledge in the aftermath of genocidal violence. As defined here, Holocaust mementos encompass everyday objects predating the Holocaust and originally belonging to Jews, objects relating to the persecution of Jews, and three-dimensional folk art that depicts the Holocaust. This article focuses on two distinct geographical and social contexts of collecting – private collections of Holocaust-themed folk art in Germany and private collections of Jewish artifacts and personal belongings in the former shtetls of Poland and Belarus. The author examines how private collections of Holocaust objects come into being and how they function. This article discusses the collectors' fascination with such objects as rare, exclusive, and emotionally charged relics whose discovery testifies to their owners' supreme expertise and dedication, as vehicles of introspective exploration, and as soterial objects that provide comfort and allow self-righteous positioning vis-à-vis a difficult past.